Historical and legal aspects of organization and functioning of bodies of pretrial proceedings in a criminal case in Belarus - Bibilo, Valentina N. (Journal of the Belarusian State University. Law, 2019)
The article considers historical and modern aspects of organization of pretrial criminal law activity. The author substantiates the conclusion about the necessity of inclusion in the legislation the concept of «initiation criminal prosecution» instead of «initiation criminal case». It is proved that the investigator performs the function of indictment, regardless of whether its procedural powers are reduced or expanded. The main task of the investigator is to gather evidence. The function of indictment performed by the investigator ends with the transfer of the criminal case to the prosecutor for the referral to the court.